(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Two conditions have to be met in order to take for granted the localization of an ancient city: the modern place must be connected with it through an exclusive and unequivocal link, and must dispose of material remains fitting the date and conditions known about the ancient city. Otherwise the localization is just an hypothesis, and should be taken only as such. That is what happens in the modern province of Teruel, where there is no ancient city which can be located with certainty. Four examples are examined: Damania, whose connection with La Muela (Hinojosa de Jarque) is probable, but not certain; Leonica and Orosis, whose localization is unsure; and Osicerda,mentioned in an inscription from La Puebla de Híjar, which is in my opinion the most firm indication for its emplacement.